Chapter 'Is it possible to represent her freshly without reproducing sexist and racist appropriation?' - Kisubi Mbasalaki, Phoebe (Amsterdam University Press, 2023)
When black South African artist Willie Bester, whose art persistently criticizes the colonial and totalitarian history of his country, created a sculpture of Sarah Bartmann (or Saartjie Bartmann) out of recycled material, one wouldn't have imagined so many ruptures from this work. Buikema (2007) clinically unpacks the first rupture at the University of Cape Town by deploying politics of representation as presence and symbolic. And she questions: Is it possible to represent Sarah Bartmann freshly without reproducing sexist and racist appropriations? In this article, I unpick Buikema's article while putting it into conversation with further ruptures that took place at UCT between 2015-2018 after the student protests calling for decolonisation of the university. I argue that it is through such critical engagements and discomforts that transformation towards dignifying and humanizing of Sarah Bartmann occurs; and by extension, epistemic justice.